Distribution of Catecholaminergic Presympathetic-Premotor Neurons in the Rat Lower Brainstem - Nam, Hyungwoo (Neuroscience, 2016)
We previously characterized the organization of presympathetic-premotor neurons (PSPMNs), which send descending poly-synaptic projections with collaterals to skeletal muscle and the adrenal gland. Such neurons may play a role in shaping integrated adaptive responses, and many of them were found within well-characterized regions of noradrenergic cell populations suggesting that some of the PSPMNs are catecholaminergic. To address this issue, we used retrograde trans-synaptic tract-tracing with attenuated pseudorabies virus (PRV) recombinants combined with multi-label immunofluorescence to identify PSPMNs expressing tyrosine hydroxylase (TH). Our findings indicate that TH-immunoreactive (ir) PSPMNs are present throughout the brainstem within multiple cell populations, including the A1, C1, C2, C3, A5 and A7 cell groups along with the locus coeruleus (LC) and the nucleus subcoeruleus (SubC). The largest numbers of TH-ir PSPMNs were located within the LC and SubC. Within SubC and the A7 cell group, about 70% of TH-ir neurons were PSPMNs, which was a significantly greater fraction of neurons than in the other brain regions we examined. These findings indicate that TH-ir neurons near the pontomesencephalic junction that are distributed across the LC, SubC, and the A7 may play a prominent role in somatomotor-sympathetic integration, and that the major functional role of the A7 and SubC noradrenergic cell groups maybe in the coordination of concomitant activation of somatomotor and sympathetic outflows. These neurons may participate in mediating homeostatic adaptations that require simultaneous activation of sympathetic and somatomotor nerves in the periphery.